Omadacycline Potentiates Clarithromycin Activity Against Mycobacterium abscessus - Bich Hanh, Bui Thi; Quang, Nguyen Thanh; Park, Yujin; Heo, Bo Eun; Jeon, Seunghyeon; Park, June-Woo; Jang, Jichan (Frontiers in Pharmacology, 2021)
Among non-tuberculous mycobacteria (NTM), Mycobacterium abscessus is a difficult respiratory pathogen to treat due to its drug resistance. In this study, we aimed to find a new clarithromycin partner that showed a synergistic effect with current anti-M. abscessus drugs, including omadacycline, amikacin, rifabutin, bedaquiline, and cefoxitine against M. abscessus. First, we determined the minimum inhibitory concentrations of all the drugs tested for M. abscessus subsp. abscessus CIP104536T using a resazurin microplate assay. Next, the best synergistic partner of clarithromycin against M. abscessus was evaluated with anti-M. abscessus drugs using an in vitro checkerboard combination assay. Among the drug combinations, omadacycline showed the best synergistic effect with clarithromycin, with a fractional inhibitory concentration index of 0.4. This synergistic effect was also observed against M. abscessus clinical isolates and anti-M. abscessus drug resistant strains. Lastly, this combination was further validated in a M. abscessus infected zebrafish model. In this model, the clarithromycin-omadacyline combined regimen significantly extended the lifespan of the M. abscessus infected zebrafish and inhibited the dissemination of M. abscessus within the zebrafish. In summation, the synergy between the two anti-M. abscessus compounds, clarithromycin and omadacycline, provided an attractive foundation for a new M. abscessus treatment regimen.